Evaluation of the potential agricultural use of biostimulated sewage sludge using mammalian cell culture assays - Sommaggio, Lais Roberta Deroldo [UNESP]; Mazzeo, Dânia Elisa Christofoletti [UNESP]; Pamplona-Silva, Maria Tereza [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2018)
Among the bioremediation processes, biostimulation is an effective methodology for the decontamination of organic waste by the addition of agents that stimulate the indigenous microbiota development. Rice hull is a biostimulating agent that promotes the aeration of edaphic systems and stimulates the aerobiotic activity of soil microorganisms. The present study aimed to evaluate the efficacy of the bioremediation and biostimulation processes in reducing the toxicity of sewage sludge (SS) and to evaluate its possible application in agriculture using cytotoxic and genotoxic assays in human hepatoma cells (HepG2). SS of domestic origin was tested as both the pure product (PSS) and mixed with soil (S) and with a stimulating agent, such as rice hull (RH), in different proportions (SS + S and SS + S + RH); we also examined different remediation periods (3 months - T1 and 6 months - T2). For the PSS sample, a significant induction of micronucleus (MN) in T2 was observed with nuclear buds in all of the periods assessed, and we observed the presence of more than one alteration per cell (MN and nuclear bud) in T1 and T2. The PSS sample caused genotoxic effects in the HepG2 cells even after being bioremediated. For the samples containing soil and/or rice hull, no toxic effects were observed in the test system used. Therefore, the addition of SS to agricultural soils should be conducted with caution, and it is important that the SS undergoes a remediation process, such as bioremediation and biostimulation treatments.
Keywords: Bioremediation; Genotoxicity; HepG2; Micronucleus; Rice hull